2020
DOI: 10.1002/hbm.24945
|View full text |Cite
|
Sign up to set email alerts
|

The effect of jet lag on the human brain: A neuroimaging study

Abstract: Jet lag is commonly experienced when travelers cross multiple time zones, leaving the wake–sleep cycle and intrinsic biological “clocks” out of synchrony with the current environment. The effect of jet lag on intrinsic cortical function remains unclear. Twenty‐two healthy individuals experiencing west‐to‐east jet lag flight were recruited. Brain structural and functional magnetic resonance studies, as well as psychological and neurohormonal tests, were carried out when participants returned from travel over si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Using computational models, Diekman and Bose (2018) report that this east‐west asymmetry stems from a combination of endogenous clock period (commonly >24 hours in humans) and external day length and predict that changes in day length may even induce jetlag when travelling from north to south 163 . On the other hand, Zhang et al (2020) reported that west‐to‐east jetlag induced brain and neuroendocrine changes that were related to jetlag symptoms 164 . Noteworthy, repeated long distance travel, as experienced by aircrews, may induce more severe health consequences than less extensive trans‐meridian travel.…”
Section: Modern Life Challenges To the Human Circadian Systemmentioning
confidence: 99%
“…Using computational models, Diekman and Bose (2018) report that this east‐west asymmetry stems from a combination of endogenous clock period (commonly >24 hours in humans) and external day length and predict that changes in day length may even induce jetlag when travelling from north to south 163 . On the other hand, Zhang et al (2020) reported that west‐to‐east jetlag induced brain and neuroendocrine changes that were related to jetlag symptoms 164 . Noteworthy, repeated long distance travel, as experienced by aircrews, may induce more severe health consequences than less extensive trans‐meridian travel.…”
Section: Modern Life Challenges To the Human Circadian Systemmentioning
confidence: 99%
“…Thus, a proper functioning of the circadian clock is critical to maintain homeostasis and physiological functions, and the perturbation of this system may result in severe pathologies including cancer 41,42 . Abnormal changes in circadian rhythms have been reported in jet lag 43 , night-shift workers 44 , cancer 45,46 , metabolic disorders 47,48 , mental disorders 49,50 , and also as a consequence of spaceflight [51][52][53] . Space travellers report circadian rhythm disruption during spaceflight, which is visible in many physiological aspects, for example shorter sleep durations 54 .…”
Section: Introductionmentioning
confidence: 99%
“…Although photoperiod cycle change can induce cognitive function deficit, it is also essential that photoperiod change can induce hippocampal shrinkage [41,42]. Hippocampal shrinkage is also the main basis for several mental diseases, including anxiety and depression [43,44].…”
Section: Social Jetlag and Brain Functionmentioning
confidence: 99%